2011
DOI: 10.1002/eji.201141832
|View full text |Cite
|
Sign up to set email alerts
|

Decreased NKp46 and NKG2D and elevated PD‐1 are associated with altered NK‐cell function in pediatric transplant patients with PTLD

Abstract: Post-transplantation lymphoproliferative disorders (PTLD) are life-threatening complications of organ transplantation caused by EBV infection and the use of chronic immunosuppression. While T cell impairment is known to play a critical role in the immunopathogenesis of EBV complications post-transplantation, the role of NK cells is still under investigation. Here we have characterized NK cell phenotype and function in peripheral blood from asymptomatic pediatric thoracic transplant patients, patients with PTLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 41 publications
6
78
2
Order By: Relevance
“…In these studies the expression of PD-1 was detected in PB NK cells derived from patients 37,38,59,60 but not from HDs. In addition, the level of expression reported was very low, thus rendering it difficult to discriminate between PD-1 1 and PD-1 2 cells and to identify a distinct subset of PD-1 1 cells.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In these studies the expression of PD-1 was detected in PB NK cells derived from patients 37,38,59,60 but not from HDs. In addition, the level of expression reported was very low, thus rendering it difficult to discriminate between PD-1 1 and PD-1 2 cells and to identify a distinct subset of PD-1 1 cells.…”
Section: Discussionmentioning
confidence: 79%
“…34,35 A constitutive or inducible expression of PD-1 has been detected in different cell populations, including T, B, and myeloid cells, 14,36 whereas little is known regarding PD-1 expression on NK cells to date. In human subjects it has been reported that NK cells from patients with multiple myeloma 37 or patients with posttransplantation lymphoproliferative disorders 38 can express low PD-1 levels. On the other hand, expression of PD-1 by resting NK cells from immunocompetent healthy subjects has been poorly defined.…”
mentioning
confidence: 99%
“…C NK cells in all donors 28,29 and was increased after IL-2 activation while IFNg had no effect on NK cell PD-1 expression (Fig. S5).…”
Section: Expression Of Inhibitory and Activating Ligands On Tumor Celmentioning
confidence: 97%
“…NK cell phenotypes (78)(79)(80)(81)(82)(83)(84). Therefore, many of the same conditions can exist at sites of viral and bacterial infection as seen in the tumor microenvironment.…”
Section: Oxphos Facilitates Cellular Longevitymentioning
confidence: 99%